Evidence of Competition Between Two Canopy Ant Species: Is Aggressive Behavior Innate or Shaped by a Competitive Environment? - Nádia Barbosa do Espírito Santo; Sérvio Pontes Ribeiro; Juliane Floriano Santos Lopes (Psyche: A Journal of Entomology)
Competition occurs in all ecological communities, although it has not always been experimentally tested as a structuring force in the distribution of species. We tested the hypothesis that the aggressiveness exhibited by Camponotus rufipes changes according to the pressures of a competitive environment. This is a dominant species in the montane forest of the Itacolomi State Park, Brazil, where Camponotus sericeiventris does not occur. Using bait traps in a field site where both species occur, (“Juiz de Fora” site) we showed that C. sericeiventris was able to remove C. rufipes workers at the same bait. In the laboratory, we used dyadic encounters to test workers from both species taken from colonies found in areas where both occur and where only C. rufipes was found. Camponotus rufipes from Itacolomi fought significantly less and was killed during the first few minutes in 60% of the events. On the other hand, the workers that co-existed with C. sericeiventris in the field were more aggressive, but less efficient fighters than the latter. This investigation demonstrated existence of competition between C. rufipes and C. sericeiventris, and also the lower aggressiveness of C. rufipes' individuals that did not co-exist in the field with C. sericeiventris.